Assess the relationship between job satisfaction, presenteeism, and intention of turnover from the prospective of the nursing staff at the primary healthcare - Aghareed Mustafa Alyamany; Alaa Mohammed Ghonim; Hessa Ahmad Assiri; Mazen Mohammed Asiri; Saad Abdullah Said Algharami Alghamdi; Majed Noor Abu Rabah; Noura Hamad Basheer Fairaq; Mansour Nasser Mansour Alhermis; Alya Siraj Zakariaa Faseh Aldeen; Fahad Adam Salem Aljahdaly (International Journal of Medical Toxicology and Legal Medicine, 2024)
One major factor contributing to the lack of health human resources is primary healthcare personnel’ turnover issues. Aim of the study: The purpose of this study is to ascertain the association between primary health care workers’ intentions to leave their jobs and workplace stress, as well as the mediating roles that presenteeism and job satisfaction play in this relationship. Method: Using quota sampling and stratified random sampling, 800 primary healthcare personnel were chosen in March 2024 from Jaddah, Saudi Arabia. Primary health care providers’ presenteeism, job stress, job satisfaction, and intention to leave were all measured using validated instruments. Results : The study participants reported a higher turnover intention, with primary health care professionals scoring 2.15 ± 1.03. There were notable disparities in sex and occupation, with primary health care providers more likely to intend to leave if they were male or a doctor. Additionally, this study found a significant negative correlation (-0.347, P < 0.001) between job satisfaction and turnover intention, a significant positive correlation (0.153, P < 0.001) between presenteeism and turnover intention. In conclusion Both the negative correlation between job satisfaction and turnover intention and the positive correlation between job stress and presenteeism and turnover intention were validated. Furthermore, our research validated the mediation function of presenteeism and job satisfaction in the association between job stress and intention to leave. This study offers empirical support for addressing the issue of primary healthcare personnel’ turnover.